Recent advances in lung transplantation - Meyer, Keith C (F1000Res, 2018)
Lung transplantation can improve quality of life and prolong survival for individuals with end-stage lung disease, and many advances in the realms of both basic science and clinical research aspects of lung transplantation have emerged over the past few decades. However, many challenges must yet be overcome to increase post-transplant survival. These include successfully bridging patients to transplant, expanding the lung donor pool, inducing tolerance, and preventing a myriad of post-transplant complications that include primary graft dysfunction, forms of cellular and antibody-mediated rejection, chronic lung allograft dysfunction, and infections. The goal of this manuscript is to review salient recent and evolving advances in the field of lung transplantation.